Implementasi Tugas Pokok dan Fungsi Satuan Reserse Narkoba Polresta Bandar Lampung - Heryani, Ani; Riawan, Rizky; Anggestaria, Rinda (e-JKPP, 2024)
The study titled "Implementation of the Main Duties and Functions of the Narcotics Investigation Unit of the Bandar Lampung Police" examines how this unit carries out its core responsibilities and what factors hinder their effectiveness. Using qualitative descriptive research, the study gathers data through interviews and document reviews to provide a detailed account of how the unit’s duties are executed in the field. Findings indicate that while the Narcotics Investigation Unit’s leadership aligns tasks with members’ backgrounds and skills according to policy, challenges remain in achieving full operational efficiency. Limited human resource capacity poses a significant barrier, requiring ongoing development for optimal performance. Hindrances include (1) occasional task mismatches with members’ roles, (2) assignments unrelated to primary duties, and (3) task overload and overlapping authorities, which can complicate task management within the unit.